1994
DOI: 10.1007/bf00224796
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in crayfish: Regional differences and changes induced by cooking

Abstract: The concentrations of Pb, Cd, Zn, Cu, Ni, Cr, Mn, Co, As, and Se were determined in the abdominal muscle and hepatopancreas from raw and cooked crayfish of Astacus astacus (L.) and Pacifastacus leniusculus (Dana), both of Swedish origin. After cooking, the concentrations of Cd, Ni, and Co in the hepatopancreas showed a decrease and the concentrations of Pb, Cu, and Mn in the abdominal muscle showed an increase. Metal and metalloid concentrations were also determined in the abdominal muscle and hepatopancreas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 11 publications
3
27
0
Order By: Relevance
“…Previous studies have been demonstrated that the process of cooking crayfish tails could affect trace metal concentrations. In particular, after cooking the concentrations of Cd and Ni showed decreases while the concentrations of Pb, Cu and Zn showed increases (Jorhem et al 1994; All these limits expressed in fresh weight have been converted to mg/kg dry weight, assuming a water content of 70 % in crayfish (Rigler and Downing 1984); thus, they were divided by a factor of 3.3…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been demonstrated that the process of cooking crayfish tails could affect trace metal concentrations. In particular, after cooking the concentrations of Cd and Ni showed decreases while the concentrations of Pb, Cu and Zn showed increases (Jorhem et al 1994; All these limits expressed in fresh weight have been converted to mg/kg dry weight, assuming a water content of 70 % in crayfish (Rigler and Downing 1984); thus, they were divided by a factor of 3.3…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern was observed in Cambarus bartoni (Bagatto and Alikhan 1987c). Marine decapods such as crabs (Charybdis longicollis), lobsters (Panulirus inflatus), and shrimp (Penaeus sp., Pleoticus muelleri, and Metapenaeus affinis) appear to have similar zinc accumulation patterns, with the hepatopancreas as the Results originally given as the concentration in a wet weight were recalculated to dry weight with the water content set at 80% for abdominal muscle and 72% for hepatopancreas (Jorhem et al 1994) b Concentration from an unpolluted (or reference) locality c Values less than the detection limit were replaced with the detection limit in calculation main storage organ (Darmono and Denton 1990;Marcovecchio 2004;Páez-Osuna et al 1995;Méndez et al 1997;Pourang and Amini 2001;Pourang et al 2004;Firat et al 2008). Most zinc was accumulated in the gills during laboratory toxicity tests in the crayfish (Lindhjem and Bennet-Chambers 2002;Martín-Díaz et al 2006).…”
Section: Zincmentioning
confidence: 99%
“…The intake from tea, coffee, and juice was estimated from data reported by Jorhem et al (1984), and used for calculation of the total intake. The Cd concentration of different foods was extracted from the literature, using Swedish data Sundström 1993, 1995;Jorhem et al 1984Jorhem et al , 1994, except for coarse-grained, whole-meal rye bread and butter, for which German data were used (Müller et al 1996). Twenty-eight persons reported use of vitaminerals.…”
Section: Methodsmentioning
confidence: 99%